Uncertainty about Federal Reserve policy and Its transmission to emerging economies: Evidence from Twitter - Peter Tillman (Asian Development Bank Institute (ADBI), 2016)
It is well known that a tightening or easing of the United States' monetary policy affects financial markets in emerging economies. This paper argues that uncertainty about future monetary policy is a separate transmission channel. We focus on the taper tantrum episode in 2013, a period with an elevated uncertainty about monetary policy, and use a data set that contains 90,000 Twitter messages ("tweets") on Federal Reserve tapering. Based on this data set, we construct a new index about monetary policy uncertainty using a list of uncertainty keywords. An advantage of this index is that it reflects uncertainty about a specific policy decision. An estimated vector autoregression (VAR) shows that uncertainty shocks lead to a fall in asset prices and a depreciation of local currencies. We also discuss the policy implications of this uncertainty channel of monetary policy transmission.
Keywords: E32; E44; E52; 330; Federal Reserve policy; monetary policy; monetary policy transmission; policy uncertainty; taper tantrum; uncertainty; uncertainty shocks; emerging economies; twitter